2017
DOI: 10.1080/03601234.2017.1292094
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide emission in relation with irrigation and organic amendments from a sweet corn field

Abstract: Soil moisture and organic matter level affects soil respiration and microbial activities, which in turn impact greenhouse gas (GHG) emissions. This study was conducted to evaluate the effect of irrigation levels (75%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Selected chemical properties of chicken manure, dairy manure, and milorganite are given in Table 2. Target N application rates of 168, 336 and 672 kg N ha −1 representing low, medium and high rates, respectively, were used based on the recommendations from previous researchers 38,44 .…”
Section: Methodsmentioning
confidence: 99%
“…Selected chemical properties of chicken manure, dairy manure, and milorganite are given in Table 2. Target N application rates of 168, 336 and 672 kg N ha −1 representing low, medium and high rates, respectively, were used based on the recommendations from previous researchers 38,44 .…”
Section: Methodsmentioning
confidence: 99%
“…Soil moisture content, which is controlled by irrigation in most agricultural soils, plays an important role in modulating the release and consumption of GHGs [39,40]. Increased plant biomass and soil microbial activity as a result of higher volume or more frequent irrigation lead to increases in CO 2 and N 2 O emissions compared to rainfed or non-irrigated soils [41]. This is because increased soil water content accelerates microbial respiration of soil organic matter, which enhances CO 2 flux [7].…”
mentioning
confidence: 99%
“…During this study, it was estimated that light pruning of tea bushes of TV1 and TV23 cultivars produced approximately 23 Mg ha −1 and 30 Mg ha −1 plant residues, respectively (Supporting Information Table S1). Schnitzer and Fares et al . observed that organic amendment at 20 Mg ha −1 leads to almost 50% increase in CO 2 emission from soil.…”
Section: Discussionmentioning
confidence: 99%